2021
DOI: 10.1097/wnr.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-Q-TOF/MS-based plasma metabolome to identify biomarkers and time of injury in traumatic brain injured rats

Abstract: Background To identify the potent metabolic biomarkers and time of injury of traumatic brain injured (TBI). Methods A total of 70 Sprague–Dawley rats were used to establish the TBI model in this study. The serum was collected at 3 h, 6 h, 12 h, 24 h, 3 days and 7 days after surgery. Ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was performed to analyze metabolic changes in the serum of the TBI rats from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Paired microbiome and metabolomics samples from the remaining 42 participants (17 in the normal group and 25 in the HPV group) were subjected to microbiome and metabolome analyses. All HPV(+) subjects had infected one of 14 high-risk HPV genotypes: 16,18,31,33,35,39,45,51,52,56,58,59, 66 and 68 (Supplementary Table 1). Seven of them had mixed infection of both low-risk and high-risk HPV (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paired microbiome and metabolomics samples from the remaining 42 participants (17 in the normal group and 25 in the HPV group) were subjected to microbiome and metabolome analyses. All HPV(+) subjects had infected one of 14 high-risk HPV genotypes: 16,18,31,33,35,39,45,51,52,56,58,59, 66 and 68 (Supplementary Table 1). Seven of them had mixed infection of both low-risk and high-risk HPV (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between placental ethylparaben and cord blood gammaglutamate transferase (GGT) and glucose levels provides a starting point for further studies on the mechanisms of uterine metabolic processes associated with parabens [50]. Glycocholine was used as a metabolic biomarker for traumatic brain injury (TBI) via assessing the duration of TBI injury [51]. Glycocholic acid metabolism was closely associated with certain strains of Bacteroides [52].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, researchers reported that GCA was able to function as a biomarker in TBI rat models to estimate the injury time. ( 25 )…”
Section: Discussionmentioning
confidence: 99%
“…function as a biomarker in TBI rat models to estimate the injury time. (25) Apart from pre-clinical results, there also have been clinical studies that connecting the decreased bile acids with neurological diseases. (17,26,27) In schizophrenia patients, TCDCA and other two bile acids were reported to be significantly decreased in plasma, and might be able to function as biomarkers.…”
Section: Discussionmentioning
confidence: 99%